EFFORTS TO IMPROVE CHILDREN'S ISLAMIC CHARACTER THROUGH MEMORIZING HADITH METHODS IN EARLY CHILDHOOD EDUCATION KEJORA DUSUN TEMPOS KUJUR VILLAGE GENGGELANG ACADEMIC YEAR 2021/2022 - Alawiyah, Tuti; Nuriani, Nani (Transpublika Publisher, 2022)
This study aims to describe efforts to improve the Islamic character of children through the method of memorizing hadith in early childhood education in the Tempos Kujur hamlet of Genggelang village. This research was conducted at Early Childhood Education in the even semester of the 2021/2022 academic year with a total of 20 students where this research is a classroom action research. The technique of memorizing hadith in an effort to improve the Islamic character of children uses props where the movements are in the form of cues and collaborate with existing themes with the methods used. While the data collection techniques are through observation, interviews, and documentation. The results of this study indicate that the inculcation of children's Islamic characters through the method of memorizing hadith in early childhood education in Tempos Kujur village, Genggelang village has increased after doing the 2nd cycle where in the first cycle there are BB 2 children, MB 8 people and BSH 10 children with classical completeness 50%. then in cycle II, BB is empty, MB is 3 children and BSH is 17 children with 85% classical completeness, this means that they are experiencing good development, because there is a 35% increase in classical completeness from cycle I to cycle II. This shows the application of the hadith memorization method in an effort to improve Islamic character. Children in Early Childhood Education in Tempos Kujur Village, Genggelang Village, are very helpful in choosing a learning method.